The Global Diffusion of Electric Vehicles : Lessons from the First Decade - Li, Shanjun (World Bank, Washington, DC, 2021)
Electrifying the transportation sector is key to reaching the goal of carbon neutrality. This paper provides a comprehensive analysis of the diffusion of passenger electric vehicles based on detailed data on model-level electrical vehicle sales across the world from 2013 to 2020. The analysis shows that the highly uneven electrical vehicle penetration across countries is partly driven by cross-country variation in incentives and especially in the availability of charging infrastructure. Investment in charging infrastructure would have been much more cost-effective than consumer purchase subsidies in promoting electrical vehicle adoption. This finding highlights the importance of expanding charging infrastructure in the next phase of deeper electrical vehicle diffusion.